THE INFLUENCE OF TRUSTWORTHINESS AND EXPERTISE TO CUSTOMER PURCHASE INTENTION FOR SAMSUNG AND APPLE PRODUCTS IN MANADO CITY - Raintung, Christian R. (Jurnal Berkala Ilmiah Efisiensi, 2016)
ABSTRACT There are some factors on the trustworthiness and expertise to customer purchase intention. This research is design to analyze the influence of trustworthiness and expertise to customer purchase intention for Samsung and Apple products in Manado city. Use the multiple regression analysis method, so the researcher can analyze the influence of the independent variable to dependent variable, which is employee performance. The independent variables in this research are trustworthiness and expertise. Based on the result on the analysis of data using multiple linear regression analysis techniques, the t test, obtained results which indicate that the influence of trustworthiness and expertise to customer purchase intention for Samsung and Apple products in Manado city. This shows that there is no significant difference for trustworthiness between Samsung and Apple smartphone products purchasing intention in Manado. There is no significant difference for expertise between Samsung and Apple smartphone products purchasing intention in Manado city. Keywords: Trustworthiness, Expertise, Customer Purchase Intention